Thermodynamics of chalcocite dissolving in solutions of flotation reagents - Shlyapov, M.R.; Amerkhanova, Sh.K.; Uali, A.S.; Omarbekov, T.B.; Belgibayeva, D.S. (KU Publ., 2022)
This work describes the formation of the ionic composition of the sorption layer during the concentration of copper-lead and pyrite-copper-zinc ore. The thermodynamics of the sorption layer of a sulfhydryl collector (sodium diisobutyl thiophosphate and potassium butyl xanthate) on the surface of chalcocite under various conditions of its oxidation has been studied using pH- and redoxometry. The nature of the change in the chalcocite electrode potential depending on the type of modifier and storage device, as well as on pH, has been experimentally clarified. The differences in the collective action of a one-component accumulator and a mixture of flotation reagents were revealed based on the thermodynamics analysis of the flotation process reactions. In addition, the optimal conditions for the flotation were determined. It was found that the quality of the concentrate is mainly influenced by two factors, such as the pulp redox potential and the pH of the medium. Mathematical equations of the optimal reagent and hydrodynamic enrichment regimes with the maximum dissolution of ore minerals in solutions of flotation reagents were modeled.
Флотациялық реагенттер қоспаларының ерітінділерінде халькозиннің еруінің термодинамикасы
Термодинамика растворения халькозина в растворах флотационных реагентов
Keywords: flotation; hydrophobicity; sorption layer of collector; the ionic composition of the pulp in a liquid phase; flotation reagents; sulfide minerals